Angle-of-arrival estimation using radar interferometry methods and applications - Holder, E. Jeff (SciTech Publishing, 2014)
The book reviews the developments in the following fields: RF interferometry; radar interferometry; probability theory; radar fundamentals; radar angle-of-arrival estimation; radar waveforms; interferometer signal processing; sparsely populated antenna arrays; interferometer angle-of-arrival error effects; and tropospheric effects.